Tumor‐associated macrophage‐derived transforming growth factor‐β promotes colorectal cancer progression through HIF1‐TRIB3 signaling. Issue 10 (23rd August 2021) - Liu, Changfu; Zhang, Weihao; Wang, Junfeng; Si, Tongguo; Xing, Wenge
Abstract: Tumor‐associated macrophages (TAMs), one of the most common cell components in the tumor microenvironment, have been reported as key contributors to cancer‐related inflammation and enhanced metastatic progression of tumors. To explore the underlying mechanism of TAM‐induced tumor progression, TAMs were isolated from colorectal cancer patients, and the functional interaction with colorectal cancer cells was analyzed. Our study found that coculture of TAMs contributed to a glycolytic state in colorectal cancer, which promoted the stem‐like phenotypes and invasion of tumor cells. TAMs produced the cytokine transforming growth factor‐β to support hypoxia‐inducible factor 1α (HIF1α) expression, thereby upregulating Tribbles pseudokinase 3 (TRIB3) in tumor cells. Elevated expression of TRIB3 resulted in activation of the β‐catenin/Wnt signaling pathway, which eventually enhanced the stem‐like phenotypes and cell invasion in colorectal cancer. Our findings provided evidence that TAMs promoted colorectal cancer progression in a HIF1α/TRIB3‐dependent manner, and blockade of HIF1α signals efficiently improved the outcome of chemotherapy, describing an innovative approach for colorectal cancer treatment. Abstract : Our findings provided evidence that tumor‐associated macrophages promoted colorectal progression in a HIF1α/TRIB3‐dependent manner, and blockade of HIF1α signals efficiently improved the outcome of chemotherapy, describing an innovative approach for colorectal cancer treatment.